Analysis of Socio-Demographic Determinants on Women's Participation in the Gig Economy - Shabrina Tya Mardika; Setiawan Fadjar, Nurman (Journal of Development Economic and Social Studies, 2026)
This study examines the sociodemographic determinants of women's participation in the gig economy in East Java Province. It aims to analyze the extent to which marital status, education level, residential area classification, generational background, and poverty status influence women's involvement in the gig economy. Using a quantitative method with a binary logistic regression approach, data were obtained from the March 2024 National Labor Force Survey (Sakernas). The results show that being married, having a low education, living in rural areas, being from Gen Z, and being poor significantly reduce women's chances of engaging in the gig economy. Conversely, women from Generation X and millennials, high school graduates, and those living in urban areas tend to have a greater chance of engaging in the gig economy labor market. Meanwhile, women with a college education have no significant impact. These findings contribute to the development of employment policies that are responsive to structural inequalities in the digital informal labor market.